Pelatihan Perangkat Pembelajaran Matematika Berbasis Kurikulum Merdeka bagi Guru PC LP Ma’arif NU Jepara - Endahwuri, Dhian; Shodiqin, Ali; Setyawati, Rina Dwi; Pramasdyahsari, Agnita Siska; Arum, Julia Puspita; Gunawan, Oktavian Wahyu (Pelita: Jurnal Pengabdian kepada Masyarakat, 2024)
In welcoming the 21st century, many changes have occurred in various aspects of life, including changes that have occurred in the field of education. One of these changes is the change in the curriculum used as a learning guide in schools. Changes to the Merdeka Belajar curriculum require teachers to follow these changes. However, some teachers are not ready to make and use it. With the PKM training activity on Making Independent Curriculum-Based Learning Tools for Mathematics Teachers, teachers are expected to be able to create independent curriculum-based learning tools and develop learning tools to meet the needs of students in the 21st century. The method for implementing PKM is by collaborating between three parties, namely Universitas PGRI Semarang as the initiator and implementer, as well as LPPM as the party that funds the implementation of PKM, and teachers at PC LP Maarif NU Jepara as PKM targets who will take part in a series of PKM activities. Technically there are 3 stages in implementing PKM activities, namely discussion and coordination to determine problems and plans for implementing activities, implementing PKM activities. From PKM activities, teachers understand more about making independent curriculum-based learning tools, the learning approaches and models used in independent curriculum-based learning tools, and authentic assessments contained in independent curriculum-based learning tools. PKM activities run well and smoothly. The teachers were very enthusiastic in participating in the training activities.